Internalization of Pancasila Values Through Semi-Military Discipline Education for Problematic Students (Case Analysis of the 2025 West Java Governor's Program) (COMPETITOR: Jurnal Pendidikan Kepelatihan Olahraga, 2025)
A serious challenge in student character development today is the rise of deviant behaviour such as brawls, gang violence, and drug abuse. To address this, the Governor of West Java, Dedi Mulyadi (2025), launched a semi-military disciplinary program for troubled students. This study analyses the effectiveness of the program in internalising Pancasila values through the lens of Pancasila and Citizenship Education. Using a qualitative case study approach, data were collected via in-depth interviews, observation, documentation, and analysed using SWOT analysis. The findings indicate that the program's main strength lies in the discipline and role modelling by instructors. These foster concrete internalisation of Pancasila values—responsibility, civility, cooperation, discipline, and national spirit. However, a key weakness is the lack of a dialogical, reflective component in the learning process. Opportunities exist for scaling the program to other regions, yet threats arise from criticisms by parents and education experts who deem militaristic methods unsuitable for youth development. The study concludes that character education should blend humanistic and militaristic approaches. For long-term success, supportive regulations and ongoing monitoring and evaluation are essential to ensure the program’s sustained effectiveness.